The effect of inducible nitric oxide synthase-ablation in pulmonary artery smooth muscle cells on cigarette smoke-induced pulmonary hypertension and emphysema development - Wu, Cheng-Yu; Justus Liebig University Giessen (My University, 2023)
Chronic obstructive pulmonary disease (COPD) is a significant health problem and, in addition to the burden for the patients, has a large socio-economic impact. Apart from airway diseases and pulmonary emphysema, COPD patients often suffer from a least mild pulmonary hypertension (PH). The major etiological factor is the inhalation of noxious gases or particulate matters, primarily from cigarette smoking and air pollution. Cigarette smoke (CS) drives COPD development through multiple cellular and molecular mechanisms, encompassing augmented immune responses, unbalanced proteases/anti-proteases, aberrant cell death/senescence and excessive nitrosative/oxidative stress. Previously, the inducible nitric oxide synthase (iNOS) was identified, from a mouse model of chronic exposure to CS, as a key enzyme responsible for pulmonary hypertension (PH) and emphysema development by causing nitrosative stress. In this animal model, CS-exposed mice showed alterations in the pulmonary vasculature way before signs of emphysema development. Such results indicate a possible interaction between the pulmonary vasculature and the alveolar compartment during CS-induced PH and emphysema development. Moreover, iNos-deletion in non-bone marrow-derived cells prevented CS-induced emphysema in mice, whereas PH was absent in CS-exposed mice lacking iNos in bone marrow-derived cells. A significant iNOS upregulation was observed in pulmonary vessels of CS-exposed mice and human COPD lungs. However, the contribution of increased iNOS expression/nitrosative stress in lung vessels to CS-induced emphysema and PH development remains unresolved. Against this background, the current study aimed to investigate the role of iNOS in pulmonary artery smooth muscle cells (PASMCs) during CS-induced PH and emphysema development. In vitro results revealed that iNOS was expressed in human PASMCs and increased upon cigarette smoke extract (CSE) exposure. Increased NO production was a consequence of iNOS upregulation, validated by employing a selective iNOS inhibitor – L-NIL, as well as by using PASMCs isolated from iNos-knockout (iNos-/-) mice. Furthermore, PASMCs and alveolar type 2 epithelial cells (AEC2s) isolated from iNos-/- mice were partially protected from CSE-induced damage. This may be associated with the reduction in NO levels. NO is one of the main contributors to nitrosative stress. Together with superoxide, it can form peroxynitrite, causing protein nitration at tyrosine residues, known as 3-nitrotyrosine (3-NT). 3-NT is not only a marker of nitrosative/oxidative stress, but can also alter cell signaling and thus can propagate disease progression. Along this line, an increased 3-NT formation was observed in the lung from patients with COPD, predominantly in pulmonary vessels and alveolar septa. To investigate the effect of iNOS in PASMCs on the development of CS-induced PH and emphysema, transgenic animals in which iNos was deleted in Acta2-positive (Acta2+) cells were employed and exposed to CS for 3 or 8 months. Neither CS, nor iNos deletion in Acta2+ cells, affected body weight and heart rate. However, CS led to an increased right ventricular systolic pressure (RVSP), a decreased ratio of pulmonary artery acceleration time and pulmonary artery ejection time (PAT/PET) and a decreased tricuspid annular plane systolic excursion (TAPSE), indicating the development of PH. This was independent of iNos-ablation in Acta2+ cells. Interestingly, right heart hypertrophy was already present in CS-exposed transgenic mice at time-point of 3 months, determined by an increased right ventricular wall thickness (RVWT), a decreased right ventricular internal diameter (RVID), and an elevated Fulton index. This is in contradiction to previous studies, in which Wt mice (C57BL/6J) showed an increased Fulton index after a longer period of CS exposure only. Possibly, this may be due to a higher strain-dependent susceptibility to CS-induced damage. Indeed, in vivo lung function parameters indicated that emphysema was developed after 3 and 8 months of CS exposure, regardless of the loss of iNos in Acta2+ cells. However, histological and designed-based stereological analyses suggested that the deletion of iNos in Acta2+ cells preserved the alveoli number and the alveolar structure in mice after 3 months of CS exposure. Such findings were absent in Acta2+ cell-specific iNos-knockout mice after 8 months of CS exposure, pointing out that Acta2+ cell-specific iNos-ablation delayed, but did not completely prevent CS-induced emphysema. This may be due to the nitrosative stress conferred by other iNOS-containing cell types, such as endothelial cells or an increased regenerative capacity when iNos was deleted in PASMCs. In conclusion, iNOS expression in PASMCs caused a large amount of NO production upon CS-exposure, which can be a main contributor for nitrosative stress and 3-NT formation in the lungs. In line with a previous study, when mice with deletion of iNos in non-bone marrow-derived cells were investigated, the loss of iNos in Acta2+ cells did not interfere with CS-induced PH development. A delayed emphysema development was observed in transgenic mice when iNos was deleted in Acta2+ cells after 3 months of CS exposure. It would be intriguing for further investigation to focus on the role of other iNOS-containing vascular cell types in CS-induced emphysema prevention, or on the effect of iNOS-ablation in PASMCs on lung regeneration.
Keywords: iNOS; COPD; PH; ddc:610